Protein NMR spectroscopy practical techniques and applications - Lian, Lu-Yun; Roberts, G. C. K. (Gordon Carl Kenmure) (Wiley, 2011)
"Nuclear Magnetic Resonance (NMR) spectroscopy is a powerful technique in structural biology for obtaining high resolution 3-D structures of proteins, second only, and complementary to X-ray crystallography. Molecules are studied in solution, where conditions are closer to what is found in the cell. It is the primary technique used to obtain information on intrinsically disordered (unfolded) proteins, since these proteins will not crystallize easily.The aim of this book is to provide the newcomer to NMR techniques with practical guidance on how to choose the right experiment, how to carry out the experiment, and how to analyse the resulting spectra. Those who are familiar with the chemical applications of NMR will also find it helpful in describing the special requirements of proteins"--